Use of asynchrony in flowering for easy and economical polyhaploid induction in wheat following Imperata cylindrica‐mediated chromosome elimination approach. Issue 2 (7th February 2013) - Chaudhary, Harinder K.; Tayeng, Tisu; Kaila, Vineeta; Rather, Shoukat A.; Hartl, L.
Abstract Wheat × Imperata cylindrica‐mediated approach of doubled haploidy breeding requires hand emasculation followed by pollination with I. cylindrica pollen. The pace of this endeavour can be enhanced by utilizing asynchronous flowering of wheat spikes by direct pollination without emasculation followed by morphological marker–assisted screening of selfed and crossed seeds. The emasculated and un‐emasculated spikes of 13 spring and six winter wheat genotypes and two triticale × wheat derivatives were pollinated with I. cylindrica pollen. The response of different genotypes for production of crossed and selfed seeds with direct pollination varied significantly within and between groups for spring and winter wheats, whereas triticale × wheat derivatives responded similarly to each other but significantly different from spring and winter wheats. Although, the proportion of pseudoseed formation was lower in case of direct pollination, yet in some genotypes, it was comparable to that of pollination after emasculation. Moreover, the response for haploid embryo induction frequency was similar in both the cases. The method of direct pollination can be utilized for easy and economical induction of haploids.